Mobile phones and telecommuting: Effects on trips and tours of Londoners - Padayhag, Grace Uayan; Schmöcker, Jan-Dirk; Fukuda, Daisuke (Journal of Transport and Land Use, 2011)
This study contributes to the existing literature on the travel behavioural effects of mobile phone possession and telecommuting by investigating the effects of both and looking at average trips and tours per day as well as tour complexity. In contrast to other studies, we investigate the effects of “informal telecommuting” defined as working from home on a PC. The data used in this study is taken from the London Area Travel Survey 2001, providing us with a large sample size of 87,148 trips. The results of our descriptive and multivariate regression analysis imply that mobile phone possession significantly and positively affects total trips made though not necessarily tour complexity. Our study provides good evidence that mobile phone possession is clearly associated to total tours made. Though telecommuting does decrease work trips, other trips like shopping or leisure trips are likely to increase. We provide further evidence that it is the simple home-work-home tours which decrease through telecommuting and which are replaced by other tour types, keeping the total tour numbers fairly constant. The effects are particularly pronounced for the part-time working population. Controlling for geographic characteristics, we further find that population density has an effect on leisure trips and tour complexity but not on the number of work or shopping trips.